Strategic evaluation of management efforts to reduce drpouts and enhance learning participation - Iswahyudi , Didik; Effendi, Yulius Rustan; Zuhriyah, Luluk Masruroh; Romadhon, Romadhon (Indonesian Research Journal in Education |IRJE|, 2025)
This study aims to identify effective evaluation management strategies to reduce school dropout rates and enhance educational participation in East Nusa Tenggara Province (ENTP), Eastern Indonesia. Employing a qualitative methodology with a case study approach, the research analyzes educational disparities between urban and rural areas and the effectiveness of current management policies and practices. Data were collected using in-depth interviews, direct observations, and document analysis. The findings were analyzed employing a modified descriptive-analytic approach. The results reveal that the primary factors contributing to school dropouts in ENTP include poverty, limited geographical accessibility, and low awareness of the value of education. While incentive-based policies and community-driven education management have yielded positive results, this study advocates for integrating contemporary educational management principles—such as Outcome-Based Education (OBE), technological innovation, and enhanced community participation. The policy recommendations emphasize the improvement of educational infrastructure, strengthening incentive mechanisms, and implementing contextually grounded strategies to advance inclusive and sustainable education in support of the Golden Indonesia 2045 vision.